2015
DOI: 10.1007/s10549-015-3586-x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and anthropometric changes in early breast cancer patients receiving adjuvant therapy

Abstract: Weight gain and metabolic changes have been related to survival of early breast cancer patients (EBC). ‘’However, factors influencing metabolism post-diagnosis are not fully understood. We measured anthropometric [body mass index (BMI), body weight, waist and hip circumferences, and waist-to-hip ratio] and metabolic (levels of insulin, glucose, H1Ac, total, HDL, and LDL cholesterol, triglycerides, and the homeostasis model assessment score [HOMA]) parameters in 433 pre- and post-menopausal women with EBC at di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 34 publications
0
44
0
2
Order By: Relevance
“…Body mass index at baseline was also associated with lower scores on several cognitive domains over time. The importance of considering BMI in breast cancer cognition studies is highlighted by recent research showing that there was an increase in body weight, waist and hip circumferences, triglyceride, and total cholesterol serum levels over 24 months in women diagnosed with breast cancer who received adjuvant therapy (Arpino et al 2015). Obesity is now recognized as a risk factor associated with reduced cognitive functioning.…”
Section: Discussionmentioning
confidence: 99%
“…Body mass index at baseline was also associated with lower scores on several cognitive domains over time. The importance of considering BMI in breast cancer cognition studies is highlighted by recent research showing that there was an increase in body weight, waist and hip circumferences, triglyceride, and total cholesterol serum levels over 24 months in women diagnosed with breast cancer who received adjuvant therapy (Arpino et al 2015). Obesity is now recognized as a risk factor associated with reduced cognitive functioning.…”
Section: Discussionmentioning
confidence: 99%
“…The pre‐ and post‐treatment weight and/or BMI were reported in seven of the eight studies. Four of the studies reported a significant increase in weight and/or BMI in response to treatment . The women included in the studies had a pretreatment BMI >25 kg/m 2 which correspond with the fact that increased weight, is a risk factor of BC.…”
Section: Discussionmentioning
confidence: 90%
“…Among the studies on the glucose metabolism, only two have follow‐up periods of more than a year, with Guinan et al having follow‐up periods of up to 40 months showing an increase in HbA1c, insulin and HOMA. Arpino et al, on a much larger cohort found no significant change in glucose or insulin with an average follow‐up time of 14 months. Several studies have tried to examine if the negative effect could potentially lead to an increase in diabetes diagnoses.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations